2010
DOI: 10.1007/s11244-010-9498-4
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Regenerable Co and Ni-Based Sorbents to Remove Hydrogen Sulfide at Middle Temperature

Abstract: To remove hydrogen sulfide from hot coal gases at middle temperature, the various sorbents were prepared by precipitation or co-precipitation method. The cobalt and nickel-based sorbents promoted with alumina showed good regeneration properties during multiple cycles. The roles of each component in the sulfidation and regeneration were discussed with the results from XRD and TPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…For the ZTCo sorbents, conversion of active components did not exceed 45% in any work cycle, while for ZTNi it was in the range 50-70% (Table 3). This observation is convergent with results presented by Park et al (2010). The degree of H 2 S removal on ZTNi increases in subsequent cycles (Fig.…”
Section: Desulphurizationsupporting
confidence: 92%
See 4 more Smart Citations
“…For the ZTCo sorbents, conversion of active components did not exceed 45% in any work cycle, while for ZTNi it was in the range 50-70% (Table 3). This observation is convergent with results presented by Park et al (2010). The degree of H 2 S removal on ZTNi increases in subsequent cycles (Fig.…”
Section: Desulphurizationsupporting
confidence: 92%
“…The XRD patterns of all sulphided sorbents show peaks of mixed metal oxides that indicate incomplete conversion of an active metal oxide to sulphided forms (tests were terminated after reaching 100 ppm H 2 S in the outlet gas). Park et al (2010) and Jun et al (2001) found Co 9 S 8 in the sulphided ZTC sorbent; however, their experiments were performed under different conditions. The X-ray diffraction patterns of the sulphided ZTNi1 and ZTNi2 (Fig.…”
Section: Desulphurizationmentioning
confidence: 94%
See 3 more Smart Citations